Quality management in the prevention of waste at construction sites - Boeriz, Thiago Almeida; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2021)
Civil construction is one of the sectors that contributes the most to Brazil’s economy, since in recent years, in view of the impact that other sectors have been suffering due to the sanitary problems experienced (COVID-19), construction was one of the pillars that supported the country’s Gross Domestic Product (GDP). The application of the "Lean Construction" philosophy, originated by the Toyota Production System (STP), brings as its main objective the possibility of reducing the waste caused by the industries’ productive processes, and for the civil construction processes, recognized as one of the biggest waste generators in the country, it is no different. This research has a qualitative approach and the technical procedure used was the case study. The results identified are the lack of a better structured and systematized management within the construction site; opportunity to foster financial gains; lack of knowledge about the Lean philosophy; lack of planning in the management of materials and transportation; lack of training of workers; lack of systemic vision of production, excess inventory and The contribution will occur through the foundation and Lean philosophy, being presented to the construction companies, a new work proposal to generate greater productivity aligned to reduce costs and general waste, thus achieving better results, and as a result will have their activities with higher quality and more competitive prices in the market.